Spathaspora brunopereirae sp. nov. and Spathaspora domphillipsii sp. nov., two d-xylose-fermenting ascosporogenous yeasts from Amazonian Forest biomes. Issue 3 (13th March 2023) - Santos, Ana Raquel O.; Souza, Gisele F. L.; Barros, Katharina O.; Alvarenga, Flávia B. M.; Lopes, Mariana R.; Souza, Láuren M. D.; Rosa, Luiz H.; Góes-Neto, Aristóteles; Morais, Paula B.; Lachance, Marc-André; Rosa, Carlos A.
Abstract : Four isolates of Spathaspora species were recovered from rotting wood collected in two Brazilian Amazonian biomes. The isolates produced unconjugated allantoid asci with a single elongated ascospore with curved ends. Sequence analysis of the ITS-5.8S region and the D1/D2 domains of the large subunit rRNA gene showed that the isolates represent two different novel Spathaspora species, phylogenetically related to Sp. boniae . Two isolates were obtained from rotting wood collected in two different sites of the Amazonian forest in the state of Pará. The name Spathaspora brunopereirae sp. nov. is proposed to accommodate these isolates. The holotype of Spathaspora brunopereirae sp. nov. is CBS 16119 T (MycoBank MB846672). The other two isolates were obtained from a region of transition between the Amazonian forest and the Cerrado ecosystem in the state of Tocantins. The name Spathaspora domphillipsii sp. nov. is proposed for this novel species. The holotype of Spathaspora domphillipsii sp. nov. is CBS 14229 T (MycoBank MB846697). Both species are able to convert d -xylose into ethanol and xylitol, a trait with biotechnological applications.